An EFL Student-Teacher's Cuir Identity: Narratives From a Pedagogical Practicum Experience - Edgar Aguirre-Garzón; Diego Ubaque-Casallas (Universidad Nacional de Colombia, 2024)
This article analyzes the cuir identity of an EFL student-teacher within the context of his pedagogical practicum. We adopt the term cuir as an analytical category to explore how notions of teacher identity and language pedagogy are mutually constructed. The paper challenges the traditional language pedagogy paradigm and its binary-disciplinary and heterosexist constructions of standardization. The findings documented that the construction of cuir emerges from the experiences in the body in oppressive situations. Also, a cuir identity is sometimes not risked on certain occasions and, in others, is enacted in transgressive ways through pedagogical practices. This study discusses how the cuir can be articulated with education, traditionally seen as a locus for normalization, dis-gendering, and dis-embodiment.